ROLE OF CELLULAR IMMUNITY IN CHRONIC HEART FAILURE WITH ISCHEMIC ETIOLOGY - J. Mouminov; U. I. Usmanov (Scholars Digest Publishing, 2024)
Currently, the importance of the role of inflammation in the pathophysiology of chronic heart failure (CHF) has been determined. It is reliably known that an increased level of circulating proinflammatory cytokines in patients with ischemic CHF correlates with the severity and prognosis of the disease. Monocytes play a key role in the inflammatory cascade and are the main source of both pro- and anti-inflammatory cytokines. An imbalance of physiological inflammation during myocardial damage and repair can lead to the formation of pathological chronic inflammation. This article discusses the role of monocytes and inflammation in CHF and its decompensation, and describes the types of cytokines and their involvement in inflammation. In addition, an analysis of the results of studies of drugs aimed at modulating the immune response in CHF is presented.
Keywords: acute decompensation of chronic heart failure, macrophages, cytokines, innate immunity, adaptive immunity.